A Combined Comparative Transcriptomic, Metabolomic, and Anatomical Analyses of Two Key Domestication Traits: Pod Dehiscence and Seed Dormancy in Pea (Pisum sp.) - Hradilová, Iveta; Trněný, Oldřich; Válková, Markéta; Cechová, Monika; Janská, Anna; Prokešová, Lenka; Aamir, Khan; Krezdorn, Nicolas; Rotter, Björn; Winter, Peter; Varshney, Rajeev K.; Soukup, Aleš; et al. (Frontiers in Plant Science, 2017)
The origin of the agriculture was one of the turning points in human history, and a central part of this was the evolution of new plant forms, domesticated crops. Seed dispersal and germination are two key traits which have been selected to facilitate cultivation and harvesting of crops. The objective of this study was to analyze anatomical structure of seed coat and pod, identify metabolic compounds associated with water-impermeable seed coat and differentially expressed genes involved in pea seed dormancy and pod dehiscence. Comparative anatomical, metabolomics and transcriptomic analyses were carried out on wild dormant, dehiscent Pisum elatius (JI64, VIR320) and cultivated, indehiscent P. sativum non-dormant (JI92, Cameor) and recombinant inbred lines (RILs). Considerable differences were found in texture of testa surface, length of macrosclereids and seed coat thickness. Histochemical and biochemical analyses indicated genotype related variation in composition and heterogeneity of seed coat cell walls within macrosclereids. Liquid chromatography– electrospray ionization/mass spectrometry and Laser desorption/ionization–mass spectrometry of separated seed coats revealed significantly higher contents of proanthocyanidins (dimer and trimer of gallocatechin), quercetin and myricetin rhamnosides and hydroxylated fatty acids in dormant compared to non-dormant genotypes. Bulk Segregant Analysis coupled to high throughput RNA sequencing resulted in identification of 770 and 148 differentially expressed genes between dormant and non-dormant seeds or dehiscent and indehiscent pods, respectively. The expression of 14 selected dormancy-related genes was studied by qRT-PCR. Of these, expression pattern of four genes: porin (MACE-S082), peroxisomal membrane PEX14-like protein (MACE-S108), 4-coumarate CoA ligase (MACE-S131) and UDP-glucosyl transferase (MACE-S139) was in agreement in all four genotypes with Massive analysis of cDNA Ends (MACE) data. In case of pod dehiscence, the analysis of two candidate genes (SHATTERING and SHATTERPROOF) and three out of 20 MACE identified genes (MACE-P004, MACE-P013, MACE-P015) showed down-expression in dorsal and ventral pod suture of indehiscent genotypes. Moreover, MACE-P015, the homologue of peptidoglycan-binding domain or proline-rich extensin-like protein mapped correctly to predicted Dpo1 locus on PsLGIII. This integrated analysis of the seed coat in wild and cultivated pea provides new insight as well as raises new questions associated with domestication and seed dormancy and pod dehiscence.